A Comprehensive Study on Phishing Attack Detection and Mitigation via Ransomware-as-a-Service (RAAS) - Ifthikhar, Nimra; Sajid, Ahthasham; Zafar, Adeel; Rahman, Atta Ur; Malik, Rida; Razzaq, Hamza (The Nucleus, 2025)
Ransomware-as-a-Service (RAAS), a new cybercriminal actor, is making ransomware attacks more potent and widespread. This research comprehensively assesses Ransomware-as-a-Service (RAAS) ecosystem phishing detection and prevention solutions. Seven studies compare RAAS-enabled phishing detection and prevention effectiveness, challenges, and trends. The findings recommend a multi-layered, context-aware approach for organizational resilience to shifting cyber threats. This thorough phishing attack detection and security study examines ransomware-as-a-service. Phishing attacks leverage human weaknesses to steal sensitive data and are becoming more sophisticated. Since RAAS makes ransomware attacks easier, even non-technical people may launch deadly ones. Money is making ransomware assaults more common and severe, putting people, organizations, and key infrastructure at risk. These new attacks must be detected and mitigated to safeguard digital assets. This study compares RAAS ecosystem phishing attack defence detection and mitigation technologies to identify strengths, weaknesses, and emerging trends.